Education policy document in the Kingdom of Saudi Arabia in achieving sustainable development (Analytical study) - Alsubhi, Wafiah Othman; Alyahyan, Maha Saleh Saad; Albeshr, Fatimah Abdallah (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the extent to which the education policy document in the Kingdom of Saudi Arabia includes the pillars of sustainable development in its dimensions (economic, social, environmental). The study relied on the descriptive analytical approach by relying on the content analysis method. The study reached many quantitative and qualitative results, the most prominent of which are: The number of times the education policy document in the Kingdom of Saudi Arabia included the pillars of sustainable development reached (95) times, Most of them were in implicit texts, and the most included pillar of sustainable development in the provisions of the education policy document in the Kingdom of Saudi Arabia is the social dimension, which received (64) repetitions, with a percentage of (67%). The economic dimension also came in second place, as it obtained (28) repetitions, at a rate of (30%), while the environmental dimension ranked third and last, as it received (3) repetitions, at a rate of (3%). The results showed how the provisions of the educational policy document in the Kingdom focused on including the content of some of its provisions (236) texts. It is relevant to the social dimension to an appropriate extent compared to the economic and environmental dimensions, as (68) items of the document were linked to the social dimension, and the items of the educational policy document in the Kingdom did not give attention to the environmental dimension, It contained phrases within three items related to the environment without including in its items any of the indicators of sustainable development related to the environmental dimension, especially those that emphasize preserving the environment, investing in renewable and clean energy resources, focusing on environmental awareness, protection from disasters and environmental risks, and other indicators related to sustainable development. It recommended The study calls for the need to update the educational policy document in the Kingdom of Saudi Arabia and include the indicators presented by the study as pillars of sustainable development in the field of education to keep pace with global changes and developments of the times.
Keywords: Saudi Arabia Education Policy Document; Development Pillars; Sustainable Development